A happy cell stays home: When metabolic stress creates epigenetic advantages in the tumor microenvironment - Hanse, Eric A.; Kong, Mei (Frontiers in Oncology, 2022)
A paradox of fast-proliferating tumor cells is that they deplete extracellular nutrients that often results in a nutrient poor microenvironment in vivo. Having a better understanding of the adaptation mechanisms cells exhibit in response to metabolic stress will open new therapeutic windows targeting the tumor’s extreme nutrient microenvironment. Glutamine is one of the most depleted amino acids in the tumor core and here, we provide insight into how important glutamine and its downstream by-product, -ketoglutarate (KG), are to communicating information about the nutrient environment. This communication is key in the cell’s ability to foster adaptation. We highlight the epigenetic changes brought on when KG concentrations are altered in cancer and discuss how depriving cells of glutamine may lead to cancer cell de-differentiation and the ability to grow and thrive in foreign environments. When we starve cells, they adapt to survive. Those survival “skills” allow them to go out looking for other places to live and metastasize. We further examine current challenges to modelling the metabolic tumor microenvironment in the laboratory and discuss strategies that consider current findings to target the tumor’s poor nutrient microenvironment.